Perbandingan Kinerja Bank Konvensional dan Bank Syariah pada Triwulan IV 2022 - Sipahutar, Kevin Andre; Pramana, Kiki; Azizah, Esyha Nur; Hasyim (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research analyzes the performance of Conventional Banks and Islamic Banks in Indonesia in the fourth quarter of 2022 using data from the official website of the Financial Services Authority (OJK). The study employs a qualitative descriptive approach. The text above discusses the performance comparison between conventional commercial banks (BUK) and Islamic banks (BUS) in several key aspects. Islamic banks show higher asset growth, reaching 15.57%, compared to the 9.42% growth in assets of conventional commercial banks. The composition of their assets also differs, with conventional banks focusing more on credit, while Islamic banks emphasize financing. Overall, both Conventional Banks and Islamic Banks demonstrate positive performance in the second quarter of 2022, with strategies such as diversified funding sources, increased productive credit, and operational efficiency being key drivers of growth amid the continually changing economic dynamics. This conclusion reflects the commitment of the banking sector to support Indonesia's economic growth.